(untitled) (Biological Sciences - PJSIR, 2021)
In the scenario of increasing global warming, heat stress received more importance. Un- fortunately, Pakistan is also in the line of most heat affected countries of the world. In this regard, wheat being a most important staple edible crop of Pakistan is highly affected by heat stress. For combating this situation, a study was carried-out on ten bread wheat genotypes viz. Moomal, Mehran, Imdad-05, Anmol- 91, Benazir, TJ-83, SKD-1, TD-1, Abadgar and Hamal at the Experimental Field, Department of Plant Breeding and Genetics, Sindh Agriculture University, Tandojam. The experiment was laid-out in a randomized complete block design (factorial arrangement) with three replications during Rabi season, 2016-17 in order to assess the response of wheat genotypes to terminal heat stress tolerance. Wheat genotypes were evaluated in two sowing dates viz., on 24th November as a normal planting and late planting on 31th December, 2016 considered as heat stress condition. The analysis of variance revealed significant differences among the genotypes under both sowing dates indicating suitability of the experiment to improve bread wheat genotypes for heat tolerance. Reductions in various traits were observed in late planting which indicated visible effects of heat stress on agro-economic traits. On an average plant height (cm), tillers/plant, spike length (cm), spikelets/spike, grains/spike, 1000-grain weight (g) and grain yield/plant (g) were declined by -4.63, -2.49, -3.04, -4.35, -16.29, -14.08 and -9.09 units respectively under the heat stress conditions, while the wheat genotypes like TJ-83, SKD-1 and Mehran showed minimum reductions under heat stress conditions for various traits suggesting their heat tolerance, nonetheless cultivars Moomal and Benazir expressed maximum declines under heat stress expressing their susceptibility to heat stress conditions. The remaining genotypes were found as moderately heat stress tolerant.